2017
DOI: 10.1007/s10096-017-2999-3
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the two-component system and cell-wall biosynthesis-related genes was associated with the reversion to daptomycin susceptibility in daptomycin non-susceptible methicillin-resistant Staphylococcus aureus

Abstract: Daptomycin (DAP) is widely used in the treatment of methicillin-resistant Staphylococcus aureus (MRSA) infection. The emergence of DAP non-susceptible MRSA strains during therapy is a major concern in clinical settings. Recent studies revealed that MRSA spontaneously reverts to a subsequent methicillin-susceptible S. aureus (MSSA) strain. However, it is not clear whether DAP non-susceptible MRSA has the ability to revert to a susceptible strain. We obtained an MRSA strain pair, DAP non-susceptible strain and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…The following primers were used: Ccl2, 5′-CTTCCTCCACCACCATGCA-3′ and 5′-CCAGCCGGCAACTGTGA-3′; Havcr1, 5′-AGGAAGACCCACGGCTATTT-3′ and 5′-TGTCACAGTGCCATTCCAGT-3′ (catalog Mm00506686; Applied Biosystems TaqMan Gene Expression Assays). Data were analyzed using the ΔΔCt method (32).…”
Section: Methodsmentioning
confidence: 99%
“…The following primers were used: Ccl2, 5′-CTTCCTCCACCACCATGCA-3′ and 5′-CCAGCCGGCAACTGTGA-3′; Havcr1, 5′-AGGAAGACCCACGGCTATTT-3′ and 5′-TGTCACAGTGCCATTCCAGT-3′ (catalog Mm00506686; Applied Biosystems TaqMan Gene Expression Assays). Data were analyzed using the ΔΔCt method (32).…”
Section: Methodsmentioning
confidence: 99%
“…HD patients with S. aureus bacteremia are known to be at notable risk for endocarditis, which is a life‐threating infectious disease . Other potential risk factors for infection include high burden of coexisting illnesses, hypoalbuminemia, immunosuppressive therapy, nephrotic syndrome, uremia, anemia, malnutrition and change of susceptibility of bacteria to antibiotics . However, the precise reasons why HD patients are susceptible to bacteremia remain to be clarified.…”
mentioning
confidence: 99%
“…In fact, a similar clinical case has been then reported in where a heterogeneous MRSA DAP resistance isolate was selected under DAP treatment followed by a susceptible DAP phenotype strain when the antibiotic treatment was changed, however, the mechanistic bases of this phenotypic conversion were not further explored ( Capone et al, 2016 ). Moreover, in a recent clinical MRSA strain pair obtained from a patient, it was demonstrated that DAP resistance reversion to a susceptible phenotype was obtained after DAP discontinuation, mechanistically associated with downregulation of cell wall associated genes ( Iwata et al, 2017 ). These observations including ours, support the common notion that DAP resistant strains have the ability to revert to susceptible once DAP treatment is discontinued and switched to an alternative antimicrobial therapy.…”
Section: Resultsmentioning
confidence: 99%